35 The ambulatory cardiology unit; reduction of admissions and patient outcomes after 1 year. (5th October 2017) - Byrne, J; Morrison, K; Trainor, W; McKeag, N; McCall, D
Abstract : Introduction: Recent developments in health service reform in Northern Ireland have seen the publication of the Bengoa Report, Systems, Not Structures, [1] which clearly states that "something very different has to happen at the delivery of care level." Maintenance of existing services is not sustainable, and new methods of managing health care needs must be developed and evaluated. In 2015, the Belfast Trust piloted an Ambulatory Cardiology Unit (ACU). The ethos of ACU was to reduce pressure on the ED by providing a unit where rapid evaluation, treatment and follow-up could be provided by the Cardiology team, and at the same time reduce in-patient admissions to Cardiology beds. Here we report on the experience of an Ambulatory Cardiology Unit during the first year of service. Methods: In order to measure the impact of the new service, a pre- post design was used for comparison with admission rates for 1 year after the initiation of ACU with admission rates in the preceding year, when there was no alternative to in-patient admission or out-patient care. In addition, a database was maintained for all ACU patients. This allowed the team to not only keep track of how many patients were seen and which conditions were treated in the ACU, but also allowed for follow-up for unscheduled care re-attendance, admission to hospital and mortality at 30 days, 6 months and 1 year. Results: Activity; 946 new patients were seen in the first year. 698 reviews were carried out within the first year, bringing the total number of patient episodes to 1644. Reduction in admissions; There was an overall decrease in cardiology admissions of 13.5% over a period of 1 year. Admissions with AF were reduced by 24% and syncope by 29%. There was a reduction of 45% in admissions with Pericarditis. Outcomes at 30 days – unscheduled re-attenders, n=60. Admissions, n=25. Admissions with same condition as originally seen in ACU, n=4 (0.4% of patients seen). Mortality n=4 – none from the same cause as original referral. Outcomes at 6 months – Unscheduled re-attenders, n=217. Admissions, n=60. Admissions with same condition as originally seen in ACU, n=12 (1.3 % of patients seen). Mortality n=12–2 from the same cause as original referral ( end-stage HF). This equates to 0.2% of all patients seen. Conclusion: Our unit has demonstrated that it has been possible to reduce admissions to cardiology in-patient beds by 13.5%, and patient outcomes indicate that the service is safe with only 1.7% admitted for the same reason as originally seen and only 0.2% mortality from the same condition as originally seen in ACU. Although this is a very small service, it has made an impact and demonstrates an alternative way of working. In the current climate, where ministers and clinicians agree that current methods of managing emergency care are unsustainable, our service represents a model which could be implemented by other specialities.